ANALISA PENGARUH KEMIRINGAN HEAD DAN VARIASI SUDUT BLADE TURBIN ULIR TERHADAP KINERJA PLTMH - I Putu Wahyu Indra Wedanta; Wayan Arta Wijaya; Lie Jasa (Jurnal SPEKTRUM, 2021)
Bali has many waterfalls which can be used as Micro Hydro Power Plant (MHPP). Ituses 2 types of turbines, one of them is screw turbine or Archimedes screw. Screw turbine isstill rare, therefore a MHPP modeling needs to be made to obtain specific data. This study willdiscuss the analysis of the influence of the Head Slope and the Variation of the Angle of theBlade of Turbine to Performance of the MHPP, to determine the torque, turbine rotation,voltage, current, power and rotation produced by the generator. Best measurement results onthe slope of the head 400 and variations in blade angle 280. Voltage, current and powerobtained by 73.8 V, 148.9 A and 10.98882 W. At the turbine speed before coupling, thegenerator is obtained 596 rpm and 304 rpm after coupling, while the generator rotation is 3863rpm. The resulting torque and efficiency are 0.3492 Nm and 14.16%.